IMPLEMENTASI PUBLIC RELATIONS DALAM MEMBANGUN BRAND AWARENESS AIESEC UNIVERSITAS ANDALAS SEBAGAI ORGANISASI KEPEMIMPINAN - Nanda Sarah Luthfiyyah; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Basically public relations has a role to bridge the relationship between the organization and also public both internal and external public, in addition public relations role as a supporter in organizational management functions and also to form the image of the organization. To form the image of an organization, it takes brand awareness or brand awareness is good. This study aims to find out how the implementation of media partnership in building brand awareness AIESEC Andalas University, then how the implementation of digital public relations in building brand awareness AIESEC Andalas University, and how the implementation of outreach in building brand awareness AIESEC Andalas University.This research uses qualitative research method by using Lasswell Communication Model. Research subjects consisted of 4 informants selected through purposive technique and 3 informants through accidental sampling technique. Data collection is done through observation, interview and documentation. To test the validity of the data writer used the method of extension of participation and triangulation.The results of this study indicate that the implementation of public relations conducted by Public Relations Department of AIESEC Andalas University uses two ways, namely physical and virtual. Physical by plunge spaciousness and face to face directly to the public. It's like, physical campaign, PR agenda, collaborating on an event, attending and sending event invitations, UKM visit and brand survey. By jumping directly and face to face directly can facilitate AIESEC in building brand awareness and proximity to engage with the involvement of young children and the community. Then virtually, like radio broadcasts, television coverage, printed news and online portals and also publishes activities undertaken by AIESEC Andalas University in various social media owned. Implementation of public relations virtually can achieve more mass due to its wide reach, so that this organization can be known by other young people who are not in the city of Padang.Key words: Implementation, Public Relations, AIESEC Andalas University